Inhibition of histone deacetylases class I improves adipogenic differentiation of human periodontal ligament cells: Inhibiting HDACs enhances adipogenesis in periodontal ligament cells - Serralta-Interian, Angelica A.; Montero del Toro, Julio; Nic-Can, Geovanny I.; Rojas-Herrera, Rafael; Aguilar-Ayala, Fernando J.; Rodas-Junco, Beatriz Adriana (Cellular and Molecular Biology, 2024)
Periodontal ligament stem cells (PDLSCs) show plasticity towards the adipogenic lineage; however, little has been done on the participation of epigenetic mechanisms. Histone acetylation is a dynamic process, though balanced by histone acetyltransferases (HATs) and histone deacetylases (HDACs) activities. This process can be halted by HDACs inhibitors, such as trichostatin A (TSA) and valproic acid (VPA). This study aimed to determine the role of HDACs class I in adipogenic differentiation of PDL cells. PDLSCs were treated with TSA at concentrations of 100, 200, and 250 nM, or VPA at 1, 4 and 8 mM. Cell viability was assessed using MTT assays. Gene expression of pluripotency markers (NANOG, OCT4, SOX2), HAT genes (p300, GCN5), and HDACs genes (HDAC1-3) was analyzed by RT-qPCR. Adipogenic differentiation was evaluated via oil red O staining, and acetylation of histone H3 lysine 9 (H3K9ac) was examined by Western blot. VPA treatment resulted in a 60% reduction in cell proliferation, compared to a 50% when using TSA. Cell viability was not affected by either inhibitor. Furthermore, both TSA and VPA induced adipogenic differentiation, through an increase in the deposition of lipid droplets and in GCN5 and p300 expression were observed. Western blot analysis showed that TSA increased H3K9ac levels on adipogenic differentiation of PDLSCs. These findings highlight the potential of HDAC inhibitors as a tool for modulating H3K9 acetylation status and thus influencing adipogenic differentiation of PDLCs.